The influence of alkaloids on oxidative stress and related signaling pathways - Macáková, Kateřina; Afonso, Rita; Saso, Luciano; Mladěnka, Přemysl (Free radical biology & medicine, 2019)
Alkaloids have always attracted scientific interest due to either their positive or negative effects on human beings. This review aims to summarize their antioxidant effects by both classical in vitro scavenging assay and at the cellular level. Since most in vitro studies used the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay, the results from those studies are summed up in the first part of the article. In the second part, available data on the effect of alkaloids on NADPH-oxidase, the key enzyme for reactive oxygen species production, at the cellular level, are summarized. More than 130 alkaloids were tested by DPPH assay. However, due to methodological differences, a direct comparison is hardly possible. It can be at least concluded that some of them were either similar to or even more active than standard antioxidants and the number of aromatic hydroxyl groups seems to be the major determinant for the activity. The data on inhibition of NADPH-oxidase activity by alkaloids demonstrated that there is little relationship to the DPPH assay. The mechanism seems to be based on inhibition of synthesis, activation or translocation of NADPH-oxidase subunits. In some alkaloids, activation of the nuclear factor Nrf2 pathway was documented to be the grounds for inhibition of NADPH-oxidase. Interestingly, many alkaloids can behave both as anti-oxidants and pro-oxidants depending on conditions and pro-oxidation might be the reason for activation of Nrf2. Available data on other "antioxidant" transcription factors FOXOs and PPARs are also mentioned.
Keywords: Oxidative Stress; signální transdukce; Signal Transduction; Alkaloids; oxidační stres; Humans; Pro-oxidant; alkaloidy; Anti-oxidant; oxidace-redukce; Reactive oxygen species; lidé; Antioxidants; zvířata; antioxidancia; 2,2-Diphenyl-1-picrylhydrazyl; NADPH-oxidase; Oxidation-Reduction; Animals